MINERAL DENSITY AND METABOLISM OF BONE TISSUE IN PATIENTS WITH CHRONIC HEART FAILURE INSUFFICIENCY OF SENIOR AGE - S. V. Topolyanskaya; I. O. Osipovskaya; L. S. Lifanova; T. A. Eliseeva; O. N. Vakulenko (SINAPS LLC, 2017)
The modern concepts about possible relationship between congestive heart failure and osteoporosis are described in the article. The results of bone mineral density and bone metabolism evaluation in very elderly patients with congestive heart failure (CHF) are presented. Bone mineral density was significantly lower in CHF-patients compared to control group (age-matched patients with similar main diseases - coronary artery disease and arterial hypertension). Largest differences were observed in proximal femur (р=0.01). Greater differences in BMD were detected in female patients (p=0.002). The reduced osteoblast function was observed in CHF-patients; mean osteocalcin level was 1.23 ng/ml in the CHF-group and 4.16 ng/ml - in the control group (p=0.03). Also increase of Beta-Cross laps (bone resorption marker) was registered in CHF-patients (p=0.003 vs control group). The significant negative correlation between tumor necrosis factor-a concentration and bone mineral density (especially in proximal femur) was detected (p=0.03). TNF-a levels were higher in CHF-patients than in the control group (p=0.04). In addition, bone mineral density values were lower in patients with low leptin level than in those with normal and high leptin concentrations (p=0.006). Noteworthy that low leptin values were detected in CHF-patients only.